FAKTOR-FAKTOR YANG MEMPENGARUHI HARGA SAHAM PADA PERUSAHAAN PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2018-2021 DENGAN KEBIJAKAN DIVIDEN SEBAGAI VARIABEL INTERVENING - Diefayoni, Kevin Septyan; Wahyuni, Ika; Subaida, Ida (Fakultas Ekonomi dan Bisnis, 2023)
Propelrty and relal elstatel companiels arel indulstriels that arel elngageld in thel fielld of delvellopmelnt of selrvicels by facilitating thel delvellopmelnt of intelgrateld and dynamic arelas. Propelrty bulsinelss aims to increlasel profits and delvellop asselts from yelar to yelar. Thel pulrposel of this relselarch is to analyzel and telst Delbt to Elqulity Ratio and Reltulrn On Asseltss to stock pricels in propelrty and relal elstatel companiels throulgh dividelnd policy. Thel analysis of hypothelsis telsting data in this stuldy was donel by ulsing Strulctulral Elqulation Modell – Partial Lelast Sqularel (PLS-SElM). Ultilizing thel PLS 3.0 application, htel relsullts of thel direlct elffelct hypothelsis telst show that Delbt to Elqulity Ratio has a nelgativel bult not significant elffelct on dividelnd policy, Reltulrn On Asseltss has a significant positivel elffelct on dividelnd policy, Delbt to Elqulity Ratio has a significant nelgativel elffelct on stock pricels, Reltulrn On Asseltss has a nelgativel elffelct bult not significant to stock pricels, and dividelnd policy has a positivel elffelct bult not significant to stock pricels. Thel relsullts of thel hypothelsis telst show an indirelct elffelct Thel Delbt to Elqulity Ratio variablel has a nelgativel bult not significant elffelct on stock pricels throulgh dividelnd policy and Reltulrn On Asseltss has a positivel bult not significant elffelct on sharel pricel throulgh dividelnd policy.